The Efektivitas Literature Review: Effectiveness of a Combination of Neuromuscular Taping and Balance Exercises on Postural Function in Patients with Peripheral Neuropathic Diabetes: Literature Review - Dewi, Asri Seftika; Budi Rahayu, Ummi; Jatmiko, Safari Wahyu (Rifa'Institute, 2026)
Introduction: Diabetic Peripheral Neuropathy is a common complication of diabetes mellitus that leads to sensory and motor impairments, reduced proprioception, and postural instability, increasing the risk of falls and functional limitations. Neuromuscular taping and balance training have been proposed as non-pharmacological interventions to improve postural function in this population. Objective: This literature review aimed to evaluate the effectiveness of the combination of neuromuscular taping and balance training on postural function in patients with diabetic peripheral neuropathy. Method: A literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses approach. Articles were identified from Publish or Perish and Google Scholar databases published between 2015 and 2025. Twelve eligible studies were selected based on predefined inclusion criteria and analyzed systematically. Result and Discussion: The reviewed studies demonstrated that balance training significantly improved static and dynamic balance, functional mobility, and reduced fall risk. Neuromuscular taping showed positive effects on balance, proprioception, and pain reduction. Studies combining neuromuscular taping with balance training reported more consistent and superior outcomes compared to single interventions, including improvements in postural stability and center of pressure parameters. Conclusion: The combination of neuromuscular taping and balance training is an effective and clinically applicable approach to improve postural function, reduce fall risk, and alleviate pain in patients with diabetic peripheral neuropathy.